Comparative Histomorphological study of small intestine between Harrier (Circus cyaneus) and Partridge (Alectoris chukka) in Iraq : Study of small intestine between Harrier and Partridge - Khayoon, Ektifaa; Reshag, Ali Faris Reshag (University of Thi-Qar Journal of agricultural research, 2024)
The current study was designed on 24 birds (12 birds for each type) In the anatomical part reported that the small intestine in both birds Harrier (Circus cyaneus) and Partridge (Alectoris chukka) consisted from 3 segments; duodenum, jejunum and ileum with no any demarcation between them. Both ratio of intestinal length to body length and of intestinal weight to body weight was higher in partridge than those in Harrier. In histological study showed in three parts of small intestine the wall was constituted of similar histological layers; these are mucosa, submucosa, muscularis and serosa. There were same in structure of these tunics but differences in several Histomorphometric measurements of each tunica. In all parts of small intestine of partridge the goblet cell more than those in Harrier and there were increasing in the number toward the end of intestine of these cell in both birds for lubricant role. Histochemically of this study showed that in crypts and villi of all small intestinal parts of both birds the secretion of goblet cell is neutral mucin in nature because it showed negative reaction to Alcian blue stain and positive to PAS stain.